JUMPA Vol.3 No.2 Juni 2016 ANALISIS HUBUNGAN KEBIJAKAN PERLINDUNGAN KONSUMEN DENGAN PENGGUNA KARTU KREDIT: ANALISIS HUBUNGAN KEBIJAKAN PERLINDUNGAN KONSUMEN DENGAN PENGGUNA KARTU KREDIT - Marfiani Sekolah Tinggi Ilmu Ekonomi YAI (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
The study aims to prove the relationship policy variable consumer protection against credit card provider that include the perception of the credit card services, credit card customer satisfaction and aspirations of consumer protection program techniques of data collection and measurement scales using two to four alternative answers are combined. The tipe of approach used in this study is correlation. The typeof statistics used are parametic, for a description using the mean standard deviation, while to look at the data analysisusing partial correlation. The study population included 30 people with the sampling technique used purposive sampling. Statistical testing using statistical package for social sciences version 16,0 widow with a significant level of p>0,5 the result that the hypothesis is accepted, it mean there is a significant relationship between policy analisys of consumer protection againt credit card provider.